Prevalence of obesity and it’s associated risk factors among policemen of Chitradurga district, Karnataka, India - B., Vijeth S.; Pasha, Ghouse; R., Vagesh Kumar S. (International Journal of Advances in Medicine, 2018)
Background: Obesity is an increasingly prevalent disease worldwide and can be regarded as a health problem among individuals of different occupations, including policemen, who are responsible for public security. Working throughout the day in stressful atmosphere produces adverse physical and psychological effects. We conducted this study to find the prevalence of obesity among policemen, if any, and to identify the associated risk factors for obesity in this population. Methods: Cross sectional study was conducted among 410 police personnel of 4 talukas of Chitradurga District, Karnataka from July 2017 to January 2018. Semi-structured questionnaire was prepared to collect the data, which consist of socio-demographic data, clinical examination findings, anthropometric measurements and biochemical investigations. At the end whoever had high risk factors, were treated for the same along with advice on healthy life style. Data entered in Microsoft Excel 2007 and analysed using SPSS software, version 20. Frequency tables, ANOVA test and chi-square test were used for analysis and interpretation. Results: There were total 392 males and 18 females. Age group was ranging from 21 years to 59 years. 201(49%) of the police officers were overweight and 45(11%) were obese. Ideal weight police men were younger than obese policemen and weighed less than obese police. There was statistical difference in BMI between the three groups of policemen. The mean TG and TC levels among overweight and obese were higher than ideal weight policemen and this difference was statistically significant. 32.9% of participants had a high TC level (≥200 mg/100 ml). Moreover, 93.4% and 84.1% had a low level of HDL-C and high level of LDL-C, respectively (<40 mg/ 100 ml and >150 mg/100 ml, respectively). 49.5% of our study participants had TG levels >150mg/100 ml. 60.5% and 42.7% had high SBP and DBP, respectively (>130 mmHg and >90mmHg). The difference between TC and HDL between different BMI groups was statistically significant. Conclusions: Obesity and hypertension are high risk factors for development of cardiovascular diseases. Early detection of the same and effective implementation of a physical fitness program, a regular balanced diet, inoculation training for managing stress can improve the life of police personnel.